Impact of psychogenic factors on motivational orientation of junior athletes - Popovych, I.; Koval, I.; Zavatska, N.; Hoi, N.; Shchyruk, I.; Domina, H.; Zinchenko, S. (Journal of Physical Education and Sport, 2023)
The purpose of the empirical research is to find out the impact of psychogenic factors on motivational orientation of junior athletes. The study identified differences in the psychological content parameters reflecting psychogenic factors of junior athletes by high and low levels. The research involved juniors (n=75) (Me=17; M=17.23; SD=±1.67) representing the following football clubs (n=43): FC "Krystal" (Kherson, Ukraine), FC "Riatuvalnyk" (Mykolaiv, Ukraine), FC "Enerhiia" (Lviv, Ukraine) and juniors (n=32) of handball clubs "Dniprianka" (Kherson, Ukraine) and "Real" (Mykolaiv, Ukraine).